Deconstructing and Historicizing Access to Medicines: The Changing Priority of Pharmaceutical Governance in China - Li, Lantian (Frontiers in Sociology, 2021)
Securing access to medicines (ATM) is critical to improving public health outcomes. Existing research has long identified and analyzed various barriers that may impede ATM at the global, national, or local levels. However, it tends to adopt a normative perspective to prescribe what infrastructures, resources, and measures should be put in place to improve ATM. Little scholarship has explored how and why countries may prioritize certain dimensions of ATM over others in pharmaceutical governance within specific historical contexts. This article fills that gap by deconstructing and historicizing the concept of ATM. I aim to make two arguments. First, tensions easily arise between different dimensions of ATM, and prioritizing certain dimensions in pharmaceutical policy may impede improvements in others (e.g., availability vs. affordability). Second, which dimension(s) of ATM might be prioritized in the state’s pharmaceutical policy hinges upon social, economic, and political forces. To substantiate my arguments, I draw on interview and archival evidence from China. Specifically, I provide a historical account of how and why the priorities of pharmaceutical governance in China changed over time: 1) 1949 – late 1970s: pursuing both drug availability and affordability through socialist planning; 2) early 1980s – 2015: priority shifting from availability (before the mid 1990s) to affordability (after the mid 1990s); 3) 2015 – present: striving for a rebalance between drug availability and affordability.